Can National Oral Health Policy Reform Be Successfully Translated into Practice and Reduce the Burden of Disease in Australia? - Md Shahidul Islam; Caitlyn Brennan (ACHSM, 2021)
BACKGROUND: The discrepancy between policy makers decisions, current research and clinical practice is of huge significance to the health industry and the Australian community.  AIM: Evaluate of translational research frameworks and policy formulation within the Australian oral health context.  METHODS: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a focused systematic search was conducted using an electronic search of the CINAHL database, including Medline, Cochrane and Scopus. A combination of key terms including "oral health", "prevention'', 'translational research', "public policy", were used for the searches.   RESULTS: The initial literature search found 561 abstracts in CINAHL database. Review against the inclusion criteria and removal of duplicates yielded 129 abstracts; further reviewed against the inclusion criteria resulted in 35 included in the review of translational research models. Across the 35 papers 8 different frameworks for translation of research evidence into policy and practice were utilised across the literature. The results reported in this studies show that the PARiHS framework depicts successful translation as a function of the relationship between evidence, context and facilitation. These interplays of elements are particularly of relevance to oral health due to the complexity of the sector. Context (current and historical) and facilitation (including governance/regulation) are the foundational drivers of successful implantation of evidence into practice.  CONCLUSION: The PARiHS framework for implementing research into practice is an appropriate model for oral health. Universal access is a feasible step in addressing the current inequities of access to oral health care.